Carbon footprint allocation among consumers and transmission losses - Pourakbari-Kasmaei, Mahdi [UNESP]; Mantovani, Jose Roberto Sanches [UNESP]; Rashidinejad, Masoud; Habibi, Mohammad Reza; Contreras, Javier (Institute of Electrical and Electronics Engineers (IEEE), 2017)
Carbon emission reduction is one of the most challenging issues in our emission-constrained world. However, a reduction may come into reality when enough information is available. Although the emissions are produced on the generation side as a result of fuel combustion, this generation is driven by demand, and consequently, the consumers are the prime responsible for carbon emissions in the electric power sector. On the generation side, providing enough information is relatively easy. It only requires economic-oriented tools such as economic dispatch and optimal power flow (OPF). However, on the demand side, providing consumers such useful information, to show them their role in emission production, requires more complicated tools and procedures. To explain and remedy this shortcoming, in this paper, we allocate the carbon footprint among the consumers as well as the transmission loss via a tracing method. To show the effectiveness and applicability of the proposed approach, two small-scale systems, 5- and IEEE 30-bus, and a very large-scale power system, the Polish 2383-bus system, are conducted. This proposal can be applied to smart demandside management aiming at carbon emission reduction.
Keywords: Carbon footprint allocation; Climate change; Optimal power flow; Power tracing